On Measuring the Benefits of Lower Transport Costs - Jacoby, Hanan G.; Minten, Bart (2012)
Despite large amounts invested in rural roads in developing countries, little is known about their benefits. This paper derives an expression for the willingness-to-pay for a reduction in transport costs from the canonical agricultural household model and uses it to estimate the benefits of a hypothetical road project. Estimation is based on novel cross-sectional data collected in a small region of Madagascar with enormous, yet plausibly exogenous, variation in transport cost. A road that essentially eliminated transport costs in the study area would boost the incomes of the remotest households--those facing transport costs of about $75/ton --by nearly half, mostly by raising non-farm earnings. This benefit estimate is contrasted to one based on a hedonic approach.